Kelayakan Masker Gel Peel-Off Kopi Robusta (Coffea Canephora) dan Gambir (Uncaria Gambir) Terhadap Kecerahan Kulit Kering - Yola, Dinda Febri; Rosalina, Linda (Jurnal Tata Rias, 2023)
Dry skin makes the skin look cracked, rough, and scaly, due to weather, environmental factors, and skin diseases. For this reason, facial skin needs antioxidants to protect it from free radical attacks that can harm the skin. Robusta coffee contains flavonoids, which can increase antioxidant activity. Gambier contains catechins, which are antioxidants. For this reason, treatment for dry skin is needed in the form of a peel-off gel mask of Robusta coffee and Gambir. This study aims to determine the feasibility of peel-off gel masks for Robusta and Gambir coffee through flavonoid content tests (laboratory tests) and organoleptic tests in the categories of texture, aroma, and stickiness. and hedonic tests (panelist preferences). This study employs quantitative research methods, including an experimental approach, with observation, documentation, and observation sheets as data collection techniques. Based on the processed data, a flavonoid content test was conducted, revealing 0.0094% (9.3951 ppm) of flavonoids in 100 g of the sample tested. These flavonoids function as antioxidants, protecting the skin from free radical attacks that can harm facial skin. The organoleptic and hedonic tests showed that the peel-off gel mask had a very thick texture, a strong aroma, and a very sticky power, which were liked by the panelists. Thus, the Robusta coffee and Gambir peel-off gel masks are suitable for use on dry skin.